Effect of Antibiotics on the Microbial Efficiency of Anaerobic Digestion of Wastewater: A Review - Xiao, Leilei; Wang, Yiping; Lichtfouse, Eric; Li, Zhenkai; Kumar, P. Senthil; Liu, Jian; Feng, Dawei; Yang, Qingli; Liu, Fanghua (Frontiers in Microbiology, 2021)
Recycling waste into new materials and energy is becoming a major challenge in the context of the future circular economy, calling for advanced methods of waste treatment. For instance, microbially-mediated anaerobic digestion is widely used for conversion of sewage sludge into biomethane, fertilizers and other products, yet the efficiency of microbial digestion is limited by the occurrence of antibiotics in sludges originating from drug consumption for human and animal health. Here we present antibiotic levels in Chinese wastewater, then we review the effects of antibiotics on hydrolysis, acidogenesis and methanogenesis, with focus on macrolides, tetracyclines, β-lactams and antibiotic mixtures. We detail effects of antibiotics on fermentative bacteria and methanogenic archaea. Most results display adverse effects of antibiotics on anaerobic digestion, yet some antibiotics promote hydrolysis, acidogenesis and methanogenesis.